Modernization of the multipurpose accelerating system VGIK-1 - Yuferov, V.B.; Sorokovoj, L.G.; Kosik, N.A.; Skibenko, E.I.; Dryj, O.S.; Artyukh, V.G.; Kholod, Yu.V.; Malets, V.F.; Mufel, E.V.; Chernyshenko, V.Ya.; Ozerov, A.N.; Buravilov, I.V.; et al. (Вопросы атомной науки и техники, 2002)
The aim of VGIK-1 modernization is the possibility of metal surface processing by ion and electron irradiation, widening a range of applied energies and beam densities, vacuum condition control. This is reached by usage of two diodes, where one of them has isolated and defocussing magnetic system and another one has plasma emitter for extraction of ions and electrons. There is also the system of plasma parameters control. Vacuum system includes the cryogenic, diffusion and titanium sorbtion pumps and mass-spectrometric system